2009
DOI: 10.1158/0008-5472.sabcs-5078
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer fear in girls: a major “side effect” of breast cancer in loved ones and a backlash of ubiquitous media coverage.

Abstract: #5078 Background: Breast cancer significantly impacts girls' lives: it affects 1:8 women and directly impacts those most influential in girls' lives (e.g. mothers, friends' mothers, teachers, coaches). Plus, girls are often exposed to powerful media messages meant to raise breast cancer awareness. Our hypothesis is that these factors could generate significant fear and misunderstanding in adolescent and pre-adolescent girls.
 Methods: To better understand the impact of breast cancer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There is evidence that many parents do share their genetic test results and information about familial risk for cancer with minor at-risk children (70)(71)(72)(73)(74)(75). This is not surprising given that children (as young as 6 yo) and adolescents in families affected by cancer are informed of their parent's cancer (76)(77)(78)(79)(80). Several studies have suggested that adolescents are aware and concerned about their own risk for cancer (70)(71)(72)(73)(74)(75)(77)(78)(79)(80)(81).…”
Section: Communication Of Genetic Risk To Minor Offspringmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that many parents do share their genetic test results and information about familial risk for cancer with minor at-risk children (70)(71)(72)(73)(74)(75). This is not surprising given that children (as young as 6 yo) and adolescents in families affected by cancer are informed of their parent's cancer (76)(77)(78)(79)(80). Several studies have suggested that adolescents are aware and concerned about their own risk for cancer (70)(71)(72)(73)(74)(75)(77)(78)(79)(80)(81).…”
Section: Communication Of Genetic Risk To Minor Offspringmentioning
confidence: 99%
“…This is not surprising given that children (as young as 6 yo) and adolescents in families affected by cancer are informed of their parent's cancer (76)(77)(78)(79)(80). Several studies have suggested that adolescents are aware and concerned about their own risk for cancer (70)(71)(72)(73)(74)(75)(77)(78)(79)(80)(81). Approximately 50% of parents who undergo BRCA1/2 testing inform at-risk minors of their genetic test result (81)(82)(83).…”
Section: Communication Of Genetic Risk To Minor Offspringmentioning
confidence: 99%